Economic Evaluation of the Use of Cefotaxime and Ceftazidime in the Treatment of Pneumonia in Pediatric Patients - Valen Ruterlin; Rano K. Sinuraya; Eli Halimah; Melisa I. Barliana; Sri Hartini (Universitas Padjadjaran, Indonesia)
The prevalence of pneumonia is particularly high among pediatric patients. Appropriate antibioticsselection is required to reduce mortality and morbidity rates associated with thesediseases. However, information on cost-effectiveness of empirical antibiotics treatment forpneumonia was limited. This study was aimed to evaluate cost-effectiveness of cefotaximeand ceftazidime for pneumonia in pediatric patients. This study was a retrospective crosssectional study conducted at a hospital in Bandung during January-December 2012. Datawere derived from medical records of pediatric pneumonia inpatients during study period.Cost was calculated based on direct medical cost, i.e., inpatient care, medical support, andmedicines that were used from admission until hospital discharge. The results showed thatthere was no statistical difference in the average medical cost of the treatment using cefotaxime(1,197,017 IDR) and ceftazidime (2,245,748 IDR). Incremental cost effectivenessratio (ICER) showed that cefotaxime is more cost effective than ceftazidime with greaterreduction of leukocytes level (576 IDR/mm3 ). The use of cefotaxime is recommended forthe treatment of pnuemonia in pediatric patients.Keywords: cost minimization, cost effectiveness, cefotaxime, ceftazidime, pneumonia